The Fate of the Deficient Souls from the View of Avicenna - Zahra Kahrizi; Abbas Ali Mansouri; Mojtaba Biglari (آموزه‌‌های فلسفه اسلامي)
The fate of the deficient souls (children, dunces and insane persons) is one the most challengeable issues of the resurrection (ma'ād) that from a long time ago has occupied the philosophers’ mind because every answer to this subject confronts special problems. If we believe that these souls have the resurrection (ma'ād) then it is difficult to explain how these souls have the reward and punishment and if we negate the resurrection (ma'ād) of these souls then it is inconsistent with some other religious declarations (formal statements) and also with some philosophical opinions that believe these souls are the owner of the incorporeal soul. The aim of this research is to study Avicenna’s opinions about the fate of these souls. Although Avicenna has not clarified the accurate and broad meaning of the deficient souls but explicitly has discussed this subject in his several books and believes that the resurrection (ma'ād) is for all people and includes the deficient souls. The principles of Avicenna’s anthropology strengthen this opinion. But concerning the quality (characteristic) of the resurrection and positions of these souls in the Last Day (Akhirah), Avicenna’s words are double-minded. Sometimes he agrees to those who believe that these souls join to heavens (al-aflak), sometimes he refers the fate of the deficient souls to the vast divine mercy, sometimes he places the deficient souls in the group of the prosperous, sometimes he believes these souls will not be assigned either to bliss or damnation and sometimes he generalizes the concept of the deficient souls and ‘the synthesis of his optimistic vision and the problem of salvation he situates majority of people within this concept.